2012
DOI: 10.1177/1087057111416659
|View full text |Cite
|
Sign up to set email alerts
|

Development of Homogeneous Nonradioactive Methyltransferase and Demethylase Assays Targeting Histone H3 Lysine 4

Abstract: Histone posttranslational modifications are among the epigenetic mechanisms that modulate chromatin structure and gene transcription. Histone methylation and demethylation are dynamic processes controlled respectively by histone methyltransferases (HMTs) and demethylases (HDMs). Several HMTs and HDMs have been implicated in cancer, inflammation, and diabetes, making them attractive targets for drug therapy. Hence, the discovery of small-molecule modulators for these two enzyme classes has drawn significant att… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

2
51
0

Year Published

2012
2012
2022
2022

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 39 publications
(53 citation statements)
references
References 34 publications
(56 reference statements)
2
51
0
Order By: Relevance
“…IC 50 values were also fairly consistent with literature values of 359 nM for sinefungin and 16 µM for SAH. 3 Both compounds showed slightly higher potency in our assay, which could be attributed to transfer of the compound via the Echo liquid handler, eliminating potential loss of compounds, particularly those with hydrophobic characteristics, from sticking to tips. [22][23][24][25] Z′ factors for the miniaturized assays were excellent-0.82 and above in the miniaturized assay volumes, in both 384-and 1536-well formats, compared to 0.73 in the manually pipetted 25 µL 384-well assay.…”
Section: Alphalisa Methyltransferase Assaymentioning
confidence: 99%
See 2 more Smart Citations
“…IC 50 values were also fairly consistent with literature values of 359 nM for sinefungin and 16 µM for SAH. 3 Both compounds showed slightly higher potency in our assay, which could be attributed to transfer of the compound via the Echo liquid handler, eliminating potential loss of compounds, particularly those with hydrophobic characteristics, from sticking to tips. [22][23][24][25] Z′ factors for the miniaturized assays were excellent-0.82 and above in the miniaturized assay volumes, in both 384-and 1536-well formats, compared to 0.73 in the manually pipetted 25 µL 384-well assay.…”
Section: Alphalisa Methyltransferase Assaymentioning
confidence: 99%
“…The plates were sealed, centrifuged for 1 s at 1000 rpm, and then incubated for 30 min at RT. Conditions were adapted from Gauthier et al 3 Anti-methyl-Histone H3 Lysine 4 (H3K4me1-21) acceptor beads were then transferred to the assay plates with the Echo 525 liquid handler to a final concentration of 20 µg/ mL. Plates were resealed, briefly centrifuged at 1000 rpm, shaken for 15 s on a Teleshake 384 (Thermo Scientific, Waltham, MA) magnetic shaker, and then incubated for 60 min at RT in the dark.…”
Section: Alphalisa Methyltransferase Assay Set7/9 Inhibitor Titrationmentioning
confidence: 99%
See 1 more Smart Citation
“…10 Recently, homogeneous nonradioactive antibody-based assays (LANCE Ultra and AlphaLISA) have been described. 11 During assay development, we investigated the use of a similar peptide-based AlphaScreen method. However, the screen described here, based on a nonwash radiometric FlashPlate assay previously described for HAT activity, 12 provided a greater signal window.…”
Section: Optimization Of Pmt Activity Assaymentioning
confidence: 99%
“…Initially, the compounds were screened in a FRET-based LANCE ultra G9a histone H3-lysine N-methyltransferase assay 26 that measures the dimethylation of a biotinylated histone H3 (1−21) peptide at lysine 9. Previous studies have suggested that EHMT1 and EHMT2 both can mono-, di-, and trimethylate histone H3 at lysine 9.…”
mentioning
confidence: 99%